News production in Malaysia: a comparison between practices in Utusan Malaysia and Sinar Harian - Siti Suriani Othman; Lee, Kuok Tiung; Liana Mat Nayan (2014)
News making in Malaysia involves distinct types of newspaper productions. This paper intends to study the practices in two Malaysian newspapers, namely Utusan Malaysia (UM) and Sinar Harian (SH). These newspapers are distinct in their own ways, in that UM is a serious and associated with the state, and SH is privately owned and non-partisan newspaper. The elements of news production examined include the considerations involved in publishing the front page news, picture selections, the presentation of entertainment news and the comparison of news angle of both newspapers. Generally, the findings indicate that each newspaper follows specific methods of determining news, although, on the surface, there are so-called =universal‘ methods of news making. Thus, the paper argues that, even when a newspaper is produced in a particular country, news making practices are specific and still bound to specific practices within a particular news organization.